Influência dos parâmetros físico-hídricos do solo na conformação das vertentes na formação Santa Maria (membro alemoa) no bairro Camobi e distrito de Pains, Santa Maria, RS - Facco, Ronaldo (2017)
The hillslopes, interfluves, thalwegs are part of the fundamental components of the relief units. The importance of studying the influence of soil in the hillslope conformation is supported by Boulet, (1988 and 1992), when he understands that the relief evolution happens through the transformations (self development) of the soils where the hidric flows have a fundamental role. The issue studied in this research is based in the observation of the occurrence of some relative padronization in the profile shapes of the hillslopes located on Santa Maria Formation (Alemoa Member), in the Peripheral Sul-rio-grandense Depression, Santa Maria city, in Camobi neighborhood and also in Pains district. This research is aimed to comprehend the influence of the physical hidric parameters of the soil (pedological cover) in the hillslopes comformation of Santa Maria Formation (Alemoa Member), in the Peripheral Sul-rio-grandense Depression, in Santa Maria city, in the central area of Rio Grande do Sul state. In order to carry out this survey, the hypothetical-deductive method was adopted, according to (Lakatos, Marconi, 2001). It was also adopted as a theoretical methodological basis, the Boulet (1978) theory, which considers the structural analysis of the pedological cover. It is concluded that the physical hidric properties of the soil influences the conformation of the convex-concave profile of the studied hillslopes.